Effect of tamarind (Tamarindus indica L.) seed on antioxidant activity, phytocompounds, physicochemical characteristics, and sensory acceptability of enriched cookies and mango juice - Natukunda, Sheilla; Muyonga, John H.; Mukisa, Ivan M. (Food Science & Nutrition, 2016)
Tamarind seeds are not consumed despite their high antioxidative activity. In this study, 0–10% tamarind seed powder (TSP) was incorporated into mango juice and cookies. Total phenolics (Folin–Ciocalteu assay), antioxidant activity (2,2-diphenyl- 1 picrylhydrazyl (DPPH) radical scavenging assay), flavonoid (aluminum chloride assay), condensed tannins content (Vanillin-HCl assay), and consumer acceptability (n = 50) of the products were determined. TSP increased the pH and viscosity and reduced titratable acidity of juice. Incorporation of TSP increased the: total phenolic content (6.84 ± 0.21 to 88.44 ± 0.8 mg GAE/100 mL); flavonoid (4.64 ± 0.03–21.7 ± 0.36 mg CE/100 mL); condensed tannins (0.24 ± 0.01–21.81 ± 0.08 mg CE/100 mL) and total antioxidant activity (4.65 ± 0.88–21.70 ± 0.03 mg VCE/100 mL) of juice. A similar trend was observed for cookies. Maximum sensorially acceptable TSP levels were 1.5% and 6%, respectively, for juice and cookies. TSP can thus be utilized as a source of natural antioxidants in food products.
Keywords: Antioxidant activity; condensed tannin; flavonoid; phenolics; phytocompounds; tamarind seed